Design of automatic side stand and spring compression control system using arduino programming - Ramanathan, S; Gowtham, S; Gugan, E; Saisaran, K; Guhan, M (IOP conference series. Materials Science and Engineering, 2020)
Motorcycles are undoubtedly heavy, which commonly poses a problem when erecting the bike onto conventional double foot kick stands as well as it seems difficult to lift the bikes. So, using side stands is better to handle while parking bike, but it makes severe injury if the stand is not released. Most of the street side accidents occur due to lagging in releasing the side stand. This work mainly aims in designing an intelligent mechanism that automatically lifts the side stand when the driver sits in the seat. By using this control system whose setup has the ignition switch, pressure sensor,relay switch, motor drive, dc motor all controlled by the Arduino uno board through the programming interface, when the ignition switch is turned on and when the person sits on the seat integrated with spring, the spring compresses and the signals the motor to turn on and hence the stand slides up. When the ignition switch is turned off and low pressure sensed the side stand automatically pulls out to withstand the two-wheeler.